Sociodemographic characteristics, social support, and family history as factors of depression, anxiety, and stress among young adult senior high school students in metro Manila, Philippines, during the COVID-19 pandemic - Serrano, Ian Marie Atasha; Cuyugan, Anne Marie Nicole; Cruz, Krischel; Mahusay, Jan Mae Ann; Alibudbud, Rowalt (Frontiers in Psychiatry, 2023)
Introduction Academic institutions must consider the students at risk for developing poor mental health and the factors influencing them. With the scarcity of literature concerning student mental health in the Philippines, this study determined the factors influencing the risk of anxiety, depression, and stress among senior high school students in Metro Manila. Methods This cross-sectional study explored the influence of sociodemographic characteristics, social support, and family history on depression, anxiety, and stress among young adult senior high school students using the Depression, Anxiety, and Stress Scale-21 (DASS-21) and the Multidimensional Scale of Perceived Social Support (MSPSS). After describing the data, regression analyses were performed. Results A total of 187 participants were recruited. Three out of five participants have a significant risk for depression. Four out of five participants were at significant risk for anxiety. One out of four participants was at risk for significant stress. Social support from a significant other and one’s family may be protective factors for significant depression among the participants. Having female sex may be a risk factor for significant anxiety. In addition, having female sex and a family history of mental disorders may be risk factors for significant stress. Discussion Social support should be strengthened among senior high school students to improve their mental well-being. Students at risk for poor mental health, including females and those with a family history of mental disorders, may need additional support in school mental health programs. Finally, further research is recommended to fully understand mental health among Filipino students.